Behavior in CHARGE syndrome. Issue 4 (30th October 2017) - Hartshorne, Timothy S.; Stratton, Kasee K.; Brown, David; Madhavan‐Brown, Shanti; Schmittel, Megan C.
Abstract : Unusual behavior is often associated with genetic syndromes, and may constitute a behavioral phenotype. In contrast to providing a psychiatric diagnosis, a behavioral phenotype describes what is unique to the behavior associated with different syndromes. While behaviors in CHARGE are as complex and variable as other aspects of the syndrome, there are some commonalities that raise the question of common sources for these behaviors. This article addresses how pain, sensory issues, and anxiety may impact the behavior of individuals with CHARGE syndrome, and how the development of self‐regulation skills might help to mitigate some of the behaviors.